Measurement of the Usability of the Posyandu Information System for Teenagers using the System Usability Scale (SUS) at the Seruni Posyandu in Tangerang City - Ahmad Sinnun; Jenie Sundari; Sulistiyah Sulistiyah (IJNMT (International Journal of New Media Technology), 2025)
Usability is a critical factor in the successful implementation of information systems, particularly in community-based health services involving adolescent users. This study aims to measure the usability level of a web-based adolescent Posyandu information system using the System Usability Scale (SUS) instrument. A quantitative descriptive method was applied by involving 10 adolescent respondents selected purposively at Posyandu Seruni, Tangerang City. Respondents were asked to complete several main task scenarios on the system and then provide their assessments through the SUS questionnaire. The results show that the average SUS score was 72.75 with a standard deviation of 10.30 and a 95% confidence interval ranging from 65.38 to 80.12. This score places the system in the “Good” category, indicating that the adolescent Posyandu information system has a fairly good level of usability and is acceptable to users. However, some respondents provided lower scores due to navigation difficulties and unclear terminology within the system. These findings provide a foundation for improving the interface and enhancing user experience in the next development stage.